2017
DOI: 10.1097/eja.0000000000000648
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative factors related to the severity of vocal cord paralysis after thoracic cardiovascular surgery

Abstract: BACKGROUNDVocal cord paralysis (VCP) is a rare complication of thoracic cardiovascular surgery. In severe cases, life-threatening airway obstruction may occur.OBJECTIVETo evaluate the incidence and severity of VCP among patients who underwent thoracic cardiovascular surgery and to identify possible risk factors.DESIGNSingle-centre retrospective review of adult patients.SETTINGOsaka University Hospital, Suita, Japan, from January 2013 to August 2015.PATIENTSWe included 688 patients in the final analysis. Preope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…It could be argued that our results regarding diabetes mellitus as a risk for VCP, do not dispute current data. Although not statistically significant, prevalence of diabetes was low at 18% in our cohort compared to 38% reported by Taenaka et al [2].…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…It could be argued that our results regarding diabetes mellitus as a risk for VCP, do not dispute current data. Although not statistically significant, prevalence of diabetes was low at 18% in our cohort compared to 38% reported by Taenaka et al [2].…”
Section: Discussioncontrasting
confidence: 87%
“…Regarding specific risk factors for VCP, previous studies have identified duration of intubation, diabetes mellitus and specific thoracic procedures such as implantation of ventricular assist devices and aortic arch repair . The contribution of the minimally invasive surgical approach used at our centre to VCP development cannot be assessed in this study and comparative data from centres using primarily the clamshell technique is currently lacking.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations